Realization of room temperature exchange bias effect in Co/NiO bilayer via all-solid-state Li-ion redox capacitor. Issue 2 (15th January 2023) - Mustafa, Zeeshan; Jabeen, Nawishta; Hassan, Najam Ul; Jelani, Mohsan; Muhammad, Adnan Qaiser; Sehar, Fatima; Nasir, Nadeem; Idrees, Asim; Hussain, Ahmad; Bajaber, Majeed A.
Abstract: The electric field-controlled exchange bias effect has drawn considerable attention of researchers as it shows great application scope in the development of modern low power consuming spintronic devices. In this research work, we have realized a reversible controlled exchange bias effect in Co / NiO heterostructures by utilizing all-solid-state Li-ion redox capacitors having antiferromagnetic electrodes, at room temperature. The nonvolatile and reversible control of exchange bias is obtained at room temperature, resulting from controlled intercalation and deintercalation of Li-ion in antiferromagnetic NiO via galvanostatic charge and discharge process. The ion migration-controlled exchange bias mechanism in Co / NiO heterostructures is studied by using various structural, electrochemical and magnetic characterizations. This work designs an approach to control the exchange bias phenomena in all-solid state magnetoionics at room temperature, which has potential importance in establishing modern spintronic devices such as magnetic random-access memories.